Main Human Rights Concerns and Typical Issues in the African System of Human Rights - Mensah, Cocou Marius (Regional Human Rights Protection Systems Outside Europe, 2026)
The African human rights system, embodied in frameworks such as the African Charter on Human and Peoples’ Rights (ACHPR) and the African Charter on the Rights and Welfare of the Child (ACRWC), represents a regional effort to safeguard the rights of African citizens, especially vulnerable populations. However, African countries continue to face significant human rights challenges. Climate change and its impact on the right to a satisfactory environment, child labour, forced marriages and gender inequality remain constant concerns. To address these, various mechanisms, such as the African Commission on Human and Peoples’ Rights (ACmHPR), the African Court on Human and Peoples’ Rights (ACtHPR) and the African Committee of Experts on the Rights and Welfare of the Child (ACERWC), have been established. Unfortunately, weak enforcement, impunity and the reluctance of states to comply with human rights judgments hinder progress. This chapter explores the legal frameworks, key issues and landmark cases within the African human rights system, emphasising the pressing need for effective implementation to protect fundamental rights across the continent.Keywords: African Charter on Human and Peoples’ Rights, African Charter on the Rights and Welfare of the Child, Environmental rights, African human rights system, Human rights enforcement